Joint involvement, disease activity and quality of life in pediatric Crohn’s disease – a cross-sectional study - Beata Derfalvi; Kriszta Katinka Boros; Doloresz Szabo; Gabor Bozsaki; Aron Cseh; Gabor Rudas; Katalin Eszter Muller; Gabor Veres (Pediatric Rheumatology Online Journal, 2022)
Abstract Background Few published data describe how joint involvement, the most prevalent extraintestinal manifestation, affects quality of life (QoL) of children with Crohn’s disease (CD). Arthritis and arthralgia rates in pediatric CD patients are reportedly 3–24% and 17–22%, respectively, but studies on pre-emptive and systematic screening of joint involvement with detailed musculoskeletal rheumatological exam are lacking. More detailed data collection on joint involvement improves our understanding of how arthropathy relates to disease activity and QoL measured by the Pediatric CD Activity Index (PCDAI) and IMPACT-III questionnaire. Our study aims were to assess joint involvement in pediatric CD and correlate it with the PCDAI and IMPACT-III. Methods In this cross-sectional, observational study, a pediatric gastroenterologist assessed consecutively-seen pediatric CD patients at a tertiary care center. Patients were screened for prevalence of current and previous arthropathy, including arthritis, enthesitis and arthralgia. A single experienced pediatric rheumatologist evaluated detailed musculoskeletal history, joint status, and modified Juvenile Arthritis Multidimensional Assessment Reports (JAMAR). PCDAI, IMPACT-III, sacroiliac MRI, and HLA-B27 genetic testing were also completed. Results A total of 82 (male:female, 1.2:1; age, 13.7 ± 3.2 years) patients were involved in this study. Mean disease duration at time of study was 21.6 ± 21 months; eight of the patients were newly-diagnosed. Of the 82 patients, 29 (35%) had evidence of arthritis; for 24 of those, this was revealed by physical exam during cross-sectional screening, and by prior documentation for the remaining five patients. Joint examination confirmed active arthritis in 8/24 (33%), active enthesitis in 1/24 (4%), and evidence of previous arthritis in 15/24 (62.5%) patients. Hip (41%) and knee (38%) joints were most commonly affected. Cumulative incidence of arthralgia was 48% (39/82), and 46% (18/39) of those patients had only arthralgia without arthritis, usually affecting the knee. Axial involvement was present in 10/82 (12%) patients. Joint involvement correlated with more severe CD disease activity, specifically higher PCDAI and lower IMPACT-III scores, and increased requirement for infliximab treatment. Sacroiliitis and HLA-B27 positivity were insignificant factors in this cohort. Conclusions When a rheumatologist performed the assessment, joint involvement in pediatric CD was more prevalent than previously reported, in this cross-sectional study. Arthritis was associated with more severe CD disease activity and lower QoL.